Social aspects in small ports tourism sustainability: Planning small ports and marinas through the lens of tourism and sustainability - Bove, Alessandro; Mazzola, Elena (TeMA - Journal of Land Use, Mobility and Environment, 2023)
The attraction of the place, the perception of services, the awareness, and the tourist satisfaction play an important role to motivate a tourist to visit and revisit a destination. Sustainability has also been receiving increasing attention and require also to promote inter-generational and intragenerational equity, to guarantee the cultural integrity and social cohesion of the communities, and to protect the environment and ecosystems. In this context, nautical tourism assesses some impacts to the economy, with the construction of port and the relative infrastructures and with all services to the boat, to the society and the local community that participate to the development and choices, and to the environment with significant potential risks. This paper focusses on small ports and marinas and investigates the real situation about services offered and the related possible tourism satisfaction for a socio-cultural sustainable development. In addition, FRAMESPORT project (FRAMEwork initiative fostering the sustainable development of Adriatic-Ionian Small PORTs) assists to these objectives collecting relevant experiences and feedbacks and developing a strategic guidance. For this reason, it has collected data from people connected to Italian and Croatian docks and are analyzed with statistic methods and georeferenced maps. The significance of the study is to understand similarities and differences of tourism in these two States and provide suggestions for a socio-cultural sustainable development.